Nitenpyram degradation in finished drinking water. (8th June 2016) - Noestheden, Matthew; Roberts, Simon; Hao, Chunyan
Abstract : Rationale: Neonicotinoid pesticides and their metabolites have been indicated as contributing factors in the decline of honey bee colonies. A thorough understanding of neonicotinoid toxicity requires knowledge of their metabolites and environmental breakdown products. This work investigated the rapid degradation of the neonicotinoid nitenpyram in finished drinking water. Methods: Nitenpyram reaction products were characterized using liquid chromatography/quadrupole time‐of‐flight mass spectrometry (LC/QTOFMS). A software algorithm that compared degraded and control samples was utilized to facilitate efficient data reduction. Fragmentation pathways for six reaction products and nitenpyram were proposed using predictive software and manual product ion analysis. Results: This study showed that nitenpyram degradation in unpreserved finished drinking water was likely the result of oxidation, hydrolysis and reaction with Cl2 . Structures for six nitenpyram reaction products were proposed that suggest the C9/C11 olefin as the key reactive site. Conclusions: Similarities between the identified nitenpyram reaction products and imidacloprid metabolites highlight the importance of this study, as the toxicity of neonicotinoids to pollinators has been linked to their metabolites. Based on the proposed reaction mechanisms, the identified nitenpyram reaction products in finished drinking water could also be present in the environment and water treatment facilities. As such, identifying these degradation products will aid in evaluating the environmental impact of neonicotinoid pesticides. Copyright © 2016 John Wiley & Sons, Ltd.